Sodium thiosulfate in the treatment of non‐uremic calciphylaxis. Issue 8 (10th May 2013) - Ning, Matthew S.; Dahir, Kathryn M.; Castellanos, Emily H.; McGirt, Laura Y.
Abstract: Calciphylaxis is a metastatic calcification‐induced vasculopathy that results in the occlusion of small blood vessels. Although calciphylaxis is normally associated with end‐stage renal disease, calciphylaxis from non‐uremic origin occurs as well. While the number of reports continues to increase, a standard treatment for non‐uremic calciphylaxis has yet to be established. Sodium thiosulfate (STS), which has been proven to be effective in the treatment of uremic calciphylaxis, shows promise; however, reports of its use in non‐uremic cases are limited. We describe a case of non‐uremic calciphylaxis in a patient with normal renal and parathyroid function who had complete resolution of disease after treatment with STS, and we review similar cases in the published work. Based on the successful outcomes detailed in this case series, STS appears to be an effective therapy for non‐uremic calciphylaxis.